VIABILIDADE DA ADIÇÃO POLIMÉRICA DE LÁTEX NATURAL NA FORMULAÇÃO DE ARGAMASSAS PARA A CONSTRUÇÃO CIVIL - Arantes, Ismara C. S.; Motta, Leila A. de C.; Salomão, Maria Cláudia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Construction is directly related to the environment using its resources or as deposit of building waste. Therefore the importance of the search for alternatives that decrease the negative impacts to the environment. Faced with this, the partial replacement of non-renewable elements with natural components, such as natural latex, has been studied and its viability is the focus of this work. Four types of mortar with the same trace were developed, with variable percentages of latex: 0%, 5%, 10% and 15%. The mortars in the fresh state had their consistency index and water retention determined. In the hardened state, 28 days after concreting, resistance to bending traction, potential adherence resistance to traction, water absorption by capillarity, specific mass and void index were determined. The latex contributed to the incorporation of air in the mixture, increasing the porosity and water absorption, reducing the compression strength of the proof- bodies. The polymer, elastic material, did not improve the resistance to traction of the mortar, however, the latex created a film that reduced the entrance of the water by capillarity.